Diagnosis of tuberculosis in an Indian population by an indirect ELISA protocol based on detection of Antigen 85 complex: a prospective cohort study - Purohit Hemant J; Kelkar Sanjivani S; Agrawal Vijay S; Ramteke Sonali S; Rajan Anju N; Kashyap Rajpal S; Taori Girdhar M; Daginawala Hatim F (BMC Infectious Diseases, 2007)
Abstract Background Diagnosis of tuberculosis (TB) remains problematic despite many new advanced diagnostic methods. A reliable and rapid diagnostic test, which could be performed in any standard pathology laboratory, would help to obtain definitive early diagnoses of TB. In the present study we describe a prospective evaluation for demonstrating Antigen (Ag) 85 complex in the sera from TB patients. Methods Indirect ELISA, employing monoclonal antibodies (mAb) against the purified Ag 85 complex, was used to demonstrate Ag 85 complex in sera from TB patients. Serum samples were obtained from 197 different groups of patients: confirmed TB {n = 24}, clinically diagnosed TB {n = 104}, disease controls {n = 49} and healthy controls {n = 20}. Receiver operating curve (ROC) was used to calculate the cut off value and comparison between TB and non-TB groups were done by the chi-square test. Results The indirect ELISA method, using an mAb against Ag 85 complex, yielded 82% sensitivity (95% confidence interval [CI] 67 to 93%) and 86% specificity (95% CI, 57 to 98%) for the diagnosis of TB. The serum positivities for Ag 85 complex in cases of confirmed and clinically diagnosed TB patients were 96% (23/24) and 79% (82/104) respectively, while the positivity for patients in the non-tuberculosis group was 14% (10/69). Conclusion The detection of Ag 85 complex in sera from TB patients by indirect ELISA using mAb against purified Ag 85 complex gives a reliable diagnosis and can be used to develop an immunodiagnostic assay with increased sensitivity and specificity.